Effect of Mn Precursors on Benzene Oxidation with Ozone Over MnOx/MCM-41 at Low Temperature - Lee, Cho Rim; Jurng, Jongsoo; Bae, Gwi-Nam; Jeon, Jong-Ki; Kim, Sang Chai; Kim, Ji Man; Jin, Mingshi; Park, Young-Kwon (AMER SCIENTIFIC PUBLISHERS, 2011)
Low temperature benzene oxidation in the presence of ozone on MnOx/MCM-41 catalysts has been studied. MnOx/MCM-41 catalysts were prepared from two different precursors, Mn(NO3)(2) and Mn(CH3COO)(2), and these samples were characterized by N-2 sorption, X-ray diffraction, X-ray photoelectron spectroscopy and temperature programmed reduction. The characterization results showed that the MnOx/MCM-41 prepared from Mn(CH3COO)(2) had higher oxygen mobility and dispersion than the MnOx/MCM-41 from Mn(NO3)(2). As a result, the MnOx/MCM-41 obtained from Mn(CH3COO)(2) showed higher catalytic activity for the oxidation of benzene using ozone; however, without ozone, the catalytic activity was negligible.
Keywords: SUPPORTED MANGANESE OXIDES; CATALYTIC-OXIDATION; PYROLYSIS